ANTESEDEN PENYERAPAN ANGGARAN BELANJA DAERAH PADA SUKU DINAS PENDIDIKAN KABUPATEN ADMINISTRASI KEPULAUAN SERIBU - Alica Saputra, Ryandana; Harnovinsah; Djaddang, Syahril (FEB Universitas Sam Ratulangi Manado, 2023)
Abstract. This research aims to analyze empirical evidence of the influence of budget planning, human resource competence and organizational commitment on regional budget absorption with the process of procuring goods and services as a moderator in the education sub-department of the Seribu Islands administrative district. The sample obtained was 85 from the education sub-department of the Seribu Islands administrative district. The research results show that budget planning influences budget absorption. The HR competency variable has no effect on budget absorption. The organizational commitment variable influences budget absorption. Procurement of goods and services can moderate the influence of budget planning on budget absorption. Procurement of goods and services cannot moderate the influence of HR competency on budget absorption. Procurement of goods and services can moderate the influence of organizational commitment on budget absorption. Abstrak Penelitian ini bertujuan untuk menganalisis bukti empiris pengaruh perencanaan anggaran, kompetensi sumber daya manusia dan komitmen oganisasi terhadap penyerapan anggaran belanja daerah dengan proses pengadaan barang dan jasa sebagai pemoderasi pada suku dinas pendidikan kabupaten administrasi kepulauan seribu. Sampel yang diperoleh 85 pada suku dinas pendidikan kabupaten administrasi kepulauan seribu. Hasil penelitian menunjukkan bahwa anggaran perencanaan berpengaruh terhadap penyerapan anggaran. Variabel kompetensi SDM tidak berpengaruh terhadap penyerapan anggaran. Variabel komitmen organisasi berpengaruh terhadap penyerapan anggaran. Pengadaan barang jasa dapat memoderasi pengaruh perencanaan anggaran terhadap penyerapan anggaran. Pengadaan barang jasa tidak dapat memoderasi pengaruh kompetensi SDM terhadap penyerapan anggaran. Pengadaan barang jasa dapat memoderasi pengaruh komitmen organisasi terhadap penyerapan anggaran